Implementasi Metode Tesseract Optical Character Recognition (OCR) pada Kasus Pengawasan Transportasi Darat - Farida Hanum; Imam Muslem; Munar Munar (Fakultas Ilmu Komputer Universitas Almuslim, 2025)
Vehicles are a means of transportation that can be used to facilitate the activity of moving from one place to another. Each vehicle has its own characteristics, namely the vehicle license plate. The vehicle license plate is the identity of a motorized vehicle that has a unique serial number in the form of numbers and letters. The license plate contains the area code, police number and related area. To be able to identify the vehicle license plate number so that it is easily recognized, the author uses the Tesseract Optical Character Recognition (OCR) method. The Tesseract Optical Character Recognition (OCR) method is a method that can convert images into text form which aims to make it easier to identify the text contained in the image. In this study, the testing process was carried out in 2 ways, namely image upload and real-time video capture. The test results using the image method produced a very good text reading success rate from images of 98%, while testing using the real-time video capture method produced a text reading success rate from images of 54.9%